Effects of a multimodal exercise program on the functional capacity of Parkinson's disease patients considering disease severity and gender - Diego Orcioli-Silva; Fabio Augusto Barbieri; Lucas Simieli; Natália Madalena Rinaldi; Rodrigo Vitório; Lilian Teresa Bucken Gobbi (Universidade Estadual Paulista (UNESP), 2014)
The purpose of this study was to investigate the effects of a multimodal exercise program (MEP) on the functional capacity of patients with Parkinson's disease (PD) according to disease severity and gender. Fourteen patients with PD participated in the study and were distributed into groups according to 1) stage of disease and 2) gender. Functional capacity was evaluated before and after 6 months of intervention. The overall PD patient group improved their coordination and strength. Men and women improved in strength performance after exercise. Men also improved on coordination. For severity of disease, the unilateral group improved in strength, while the bilateral group improved in strength, balance, coordination and the UPDRS-functional score. In conclusion, a MEP is efficient in improving components of functional capacity in patients with PD, especially in strength. Gender may be considered in the exercise program. Individuals in the bilateral disease group appeared to benefit more from exercise.